Managerial advice-taking - Sharing responsibility with (non)human advisors trumps decision accuracy - Florian Aschauer; Matthias Sohn; Bernhard Hirsch (European Management Review, 2023)
Organizations are increasingly implementing algorithmic decision aids to advise managerial decision-making. We study managers' motives behind using advice (human and nonhuman), particularly sharing responsibility versus increasing decision accuracy motives. We conduct an online experiment with experienced managers in a sales forecasting setting and find that managers focus on increasing decision accuracy (sharing responsibility) when they are unable (able) to share responsibility with advisors. Moreover, managers prefer to share responsibility with blamable human advisors over nonhuman advisors unless they perceive algorithms as socially competent. Consequently, the results show that managers are not solely motivated to minimize forecast errors but also to reduce personal responsibility when taking advice. We contribute to the literature by highlighting the opportunistic motives of managers when taking (non)human advice. Our findings also bear important implications for practice. Specifically, firms should be aware of managers' opportunistic advice-taking motives when implementing algorithmic decision aids.
Keywords: 650; algorithm aversion; blame avoidance; experiment; forecasting; human judgment; judgmental adjustment